Finite Laplace transformation - Buschman, R. G. (Rev. Téc. Fac. Ing. Univ. Zulia)
Over the years several authors have obtained various properties of the Laplace transformation with the integration restricted to a finite interval. We discuss the operational properties and illustrate their applications to a boundary value problem for each an ordinary and a partial differential equation problem. The compatibility conditions which arise from the property that the transform is an entire function play a key role in applications to these boundary value problems.